Cytotoxic Effects of Ochratoxin A in Neuro-2a Cells: Role of Oxidative Stress Evidenced by N-acetylcysteine - Bhat, Pratiksha V.; Pandareesh,; Khanum, Farhath; Tamatam, Anand (Frontiers in Microbiology, 2016)
Abstract Ochratoxin-A (OTA), is toxic secondary metabolite known to cause wide range of toxic effects like nephrotoxicity, hepatotoxicity. However, the information available currently regarding neurotoxic effects exerted by OTA is scanty. Hence, the present study was aimed to evaluate the neurotoxic effects of OTA and the possible mechanisms of toxicity as well as the role of cytotoxic oxidative stress on neuronal (Neuro-2a) cell line was evaluated in vitro. Results of the MTT and LDH assay showed that, OTA induced dose-dependent cell death in Neuro-2a cells and Ic50 value was determined as 500nmol. OTA induced elevated levels of reactive oxygen species (ROS) and high levels of malondialdehyde, also loss of mitochondrial membrane potential was observed in a dose depended manner. Effects of OTA on ROS induced chromosomal DNA damage was assessed by Comet assay and plasmid DNA damage assay in which increase in DNA damage was observed in Neuro-2a cells by increasing the OTA concentration. Further western blotting analysis of OTA treated Neuro-2a cells indicated elevated expression levels of c-Jun, JNK3 and cleaved caspase-3 leading to apotptotic cell death. Other hand realtime-Q-PCR analysis clearly indicates the suppressed expression of neuronal biomarker genes including AChE, BDNF, TH and NOS2. Further N-acetylcysteine (NAC) pretreatment to Neuro-2a cells followed by OTA treatment clearly evidenced that, the significant reversal of toxic effects exerted by OTA on Neuro-2a cells. Results of the present study, reveals that ROS is the principle event in prompting increased OTA toxicity in Neuro-2a cells. However further in-vivo animal studies are in need to conclude the present study reports and the use of NAC as a remedy for OTA induced neuronal stress.